Paradigma Pengusaha Muslim terhadap Penyerapan Zakat Maal di Kabupaten Indramayu - Mohammad Wildan Alghifari Zain; Neng Dewi Himayasari (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The background of this research is to explore the paradigm of Muslim entrepreneurs towards zakat maal in Indramayu Regency and how the absorption of potential muslim entrepreneurs zakat maal in Indramayu. This study use the theory of zakat according to Imam 4 Mazhab and the theory from Yusuf Qardhawi. The purpose of this study is to find out the paradigm of Muslim entrepreneurs in Indramayu Regency about zakat maal, also the reasons why Muslim entrepreneurs in Indramayu Regency manage their zakat not through amyl institutions, and the role of amyl towards optimizing zakat maal. The method is normative descriptive analysis with a qualitative approach. The results show that the understanding of Muslim entrepreneurs in Indramayu Regency about zakat maal is varied but the majority are still very lacking, there are several factors that cause Muslim entrepreneurs not to manage their zakat through amil zakat, including: still many people that touched by socialization, religiosity factors (understanding zakat maal), belief factors, and distance factors. The role of amyl towards optimizing zakat maal is to have socialization to villages in the